Improvements of Quality Criteria for Passiflorae herba in the European Pharmacopoeia: Comparison between the 10.0 and 11.0 Edition (CIPEEX, 2025)
This study compares the monographs of Passiflorae herba in the 10.0th and 11.0th editions of the European Pharmacopoeia, identifying relevant changes for the standardization and quality control of the herbal drug. To carry out the comparison, the definition, identification specifications, tests, and quantification methods described in both editions were analyzed documentally. In the results, Ph. Eur. 10.0 describes only the dried aerial parts of Passiflorae herba, with a minimum content of 1.5% total flavonoids, expressed as vitexin, while Ph. Eur. 11.0 specifies two distinct chemotypes — swertisin or isovitexin — or their mixture, with a minimum content of 1.0% total flavonoids, expressed as isovitexin; the identification section presents a more detailed microscopic characterization of plant structures — leaves, stems, flowers, and fruits — and replaces conventional thin-layer chromatography with high-performance thin-layer chromatography, which employs homoorientin, isovitexin, and orientin as new markers; the limits for total ash and loss on drying remain unchanged; and the assay changes from spectrophotometry at 401 nm to High-Performance Liquid Chromatography, which uses isovitexin CRS as the reference standard, establishes system suitability criteria, and defines a reporting threshold, thereby increasing reproducibility and selectivity. In conclusion, the European Pharmacopoeia 11.0 introduces modifications that represent advances with a direct impact on the quality and reliability of analyses. It adopts High-Performance Liquid Chromatography instead of spectrophotometry, which increases selectivity and reduces interference, making the assay more robust. It also incorporates multiple flavonoid markers, which provide greater accuracy in the identification of the herbal drug and in chemotype differentiation. Furthermore, it promotes the international harmonization of methodologies, supporting the standardization of phytotherapy and strengthening regulatory assurance and reproducibility across laboratories.
Keywords: Passiflorae herba; European Pharmacopoeia; Chromatography